Two Systems of Good? – a Phenomenon of Proficiency - Doda-Wyszyńska, Agnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
In this article two systems of understanding of good are presented: first, the philosophical one (connected with ethical system), and second – religious one (espe cially in case of Christianity, but also other monotheistic religions). It is possible, of course, to imagine a “mixed” system or one where those two could meet each other in specific point, or concept, or representation. In general, those systems have to be considered separately. Rational explanation is crucial for a philosophical system (achieving a specific good makes a reinterpretation of ethical situation from different point of view, for example as a sacrifice, impossible), while religious system needs a personal explanation (ethical situation could have a far-reaching consequences for interpersonal relations, because a supernatural factor, for example a grace, is included here).